Tribunals (Scotland) Act 2014 : consultation on draft regulations regarding: (1) the transfer of functions and members of the Scottish Charity Appeals Panel to the Scottish Tribunals; (2) the rules of procedure for the First-tier Tribunal for Scotland General Regulatory Chamber Charity Appeals; (3) the composition of the First-tier and Upper Tribunals for Scotland and (4) the eligibility for Ordinary Membership of the First-tier Tribunal for Scotland General Regulatory Chamber.: consultation on draft regulations regarding: (1) the transfer of functions and members of the Scottish Charity Appeals Panel to the Scottish Tribunals; (2) the rules of procedure for the First-tier Tribunal for Scotland General Regulatory Chamber Charity Appeals; (3) the composition of the First-tier and Upper Tribunals for Scotland and (4) the eligibility for Ordinary Membership of the First-tier Tribunal for Scotland General Regulatory Chamber. (2017) - Unknown
No abstract available